Efektivitas Teknik Modeling Simbolik terhadap Self-esteem Siswa SMP dalam bingkai Bimbingan Kelompok - Reza Pahlevi; Anisa Oktavia (Indonesian Journal of Guidance and Counseling Studies, 2024)
Background: Self-esteem plays a crucial role in students’ academic and social development. Many junior high school students experience challenges related to self-confidence and self-worth, which can affect their overall well-being and performance in school. Counseling strategies that incorporate visual and behavioral modeling may help improve these aspects. Objective: This study aimed to determine the effectiveness of group counseling services using symbolic modeling techniques in improving the self-esteem of eighth-grade students at SMPN 5 Cimahi. Method: The research employed a quantitative approach with a quasi-experimental design, specifically the non-equivalent control group design. The study involved 20 eighth-grade students who were divided into an experimental group and a control group. Data were collected using a self-esteem questionnaire based on Christopher J. Mruk's theory. The data analysis was conducted using SPSS version 25, applying gain score calculations to measure changes in self-esteem. Result: The findings revealed that the experimental group showed an average n-gain score of 74.9%, which falls into the moderately effective category. In contrast, the control group had an average n-gain score of only 0.6%, categorized as ineffective. These results indicate a notable improvement in the self-esteem of students who participated in the symbolic modeling-based group counseling sessions. Conclusion: Group counseling services using symbolic modeling techniques are quite effective in enhancing the self-esteem of eighth-grade students at SMPN 5 Cimahi. The intervention helped students build a stronger sense of self through observational learning and social reinforcement. Contribution: This study contributes to the field of educational counseling by offering empirical evidence supporting symbolic modeling as an effective technique for improving adolescent self-esteem. It also provides a practical framework for school counselors seeking innovative methods to address students’ emotional and psychological development.